POLITIK IDENTITAS DAN RESOLUSI KONFLIK TRANSFORMATIF - Purwanto, Purwanto (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
This article aims at describing the values of pluralism and its basic principles. Multiculturalism as the doctrine of 'common culture' provides space for achievement of two needs: (1) the maintenance of diversity and integration at the level of community; (2) sustainability of unity at the level of the nation in order to achieve the goals as a nation. Multiculturalism approach is an alternative approach to politics of identity as well as an alternative to conflict resolution. Multiculturalism with pro-existence approach is conflict resolution strategy which is able to transform the tension in democracy and plurality into a new social order which gives chance for the presence of a productive interaction among diverse identities and the same time provides social integration to assure the sustainability of the principles of democracy and human rights.